IMPLEMENTASI GERAKAN LITERASI SEKOLAH MELALUI KEGIATAN READING TIME BAGI SISWA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) through Reading Time activities and to examine the reading ability and reading interest of fifth-grade students after the implementation of the program at SDN Ngagelrejo 1/396 Surabaya. This research employed a qualitative approach with a descriptive design. The research subjects consisted of fifth-grade students, classroom teachers, and the school librarian. Data were collected through observation, interviews, questionnaires, and written tests. Data validity was ensured through source and technique triangulation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that Reading Time activities were implemented routinely for approximately 15 minutes before lessons and were in accordance with the habituation stage of the School Literacy Movement, supported by teachers and the librarian as facilitators. The results of the written tests indicated an improvement in students’ reading ability, particularly in understanding and retelling the intrinsic elements of texts. In addition, questionnaire and interview results revealed an increase in students’ reading interest, as indicated by their enjoyment of reading, enthusiasm during the activities, and increased motivation to read both at school and at home. Therefore, the implementation of the School Literacy Movement through Reading Time has a positive impact on students’ reading ability and reading interest and should be carried out consistently and sustainably to foster a literacy culture in elementary schools